2017
DOI: 10.1371/journal.pone.0180132
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bone mineral density and alcohol intake: A nationwide health survey analysis of postmenopausal women

Abstract: ObjectivesAmong a variety of relevant factors of osteoporosis, the association between alcohol intake and postmenopausal women’s bone mineral density (BMD) by using data from the Korean National Health and Nutrition Examination Survey was evaluated in this study.Materials and methodsAmong a total of 31,596 subjects, males, premenopausal women, participants without BMD data were excluded. Finally, a total number of subjects in the study was 3,312. The frequency and amount of alcohol intake were determined by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…Garddini et al [10] defined moderate drinking as the regular (≥3 d/week) consumption of ≤14 g/d EtOH for women and ≤28 g/d EtOH for men, suggesting that light to moderate alcohol consumption may exert beneficial effects on aBMD, but heavy alcohol consumption has negative effects on bone quality. Our results are partially in agreement with previous findings reporting beneficial effects on aBMD (≥2 times per week) [10,14,19]. This could occur, in part, due to decreased bone resorption [41].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Garddini et al [10] defined moderate drinking as the regular (≥3 d/week) consumption of ≤14 g/d EtOH for women and ≤28 g/d EtOH for men, suggesting that light to moderate alcohol consumption may exert beneficial effects on aBMD, but heavy alcohol consumption has negative effects on bone quality. Our results are partially in agreement with previous findings reporting beneficial effects on aBMD (≥2 times per week) [10,14,19]. This could occur, in part, due to decreased bone resorption [41].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the highest aBMD was exhibited in postmenopausal women (mean 62.8 ages) who drank 2-3 times per week compared to the non-drinkers [19]. In terms of volumetric BMD (vBMD, g/cm 3 ) measured by high-resolution peripheral quantitative computed tomography, Paccou et al [17] found that men (mean 76.1 years) who consumed low amounts of alcohol had a lower vBMD, but women (mean 76.5 years) with moderate/high alcohol intake had a significantly higher vBMD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…High consumption of alcohol is expected to have a negative effect on BMD. 60,61 Higher calcium intake is associated with decreased bone loss, but alcohol consumption is correlated with low calcium level and bone loss. However, when both alcohol and calcium intake are high, decreased bone loss is observed.…”
Section: Lifestylementioning
confidence: 99%
“…Alcohol consumption affects bone metabolism, bone mass, and bone strength. Light alcohol consumption provides several beneficial effects to bone 12,13 , whereas heavy CAC is detrimental to bone and is known to induce secondary osteoporosis 13,14 . The decrease in bone mass and strength following CAC might be due to bone remodeling imbalance with a predominant decrease in bone formation 14,15 .…”
Section: Introductionmentioning
confidence: 99%